Finite element analysis of rectangular reinforced concrete columns wrapped with FRP composites - Gora, Abdurra'uf Mukhtar; Jaganathan, Jayaprakash; Anwar, M.P.; Alengaram, U. Johnson (2018)
Fibre reinforced polymer (FRP) wrapping of reinforced concrete (RC) columns has increasingly become the most suitable method used to strengthen and rehabilitate RC columns. It is clear that limited studies have investigated the behaviour of eccentrically loaded RC columns wrapped with FRP composites. In the present study, a three-dimensional finite element (FE) model was developed to simulate the behaviour of rectangular RC columns wrapped with glass fibre-reinforced polymer (GFRP) sheets under concentric and eccentric loading. The FE model was developed in the finite element analysis software ANSYS. The variables within the FE model are the number of GFRP layers and the magnitude of load eccentricity. The FE analysis results showed that GFRP wrapping significantly improved the performance of the strengthened columns by delaying concrete rupture. The presence of load eccentricity reduced the load carrying capacity and performance of the strengthened RC columns. The FE model correlated well with the stress distribution trends observed in the literature.